Ok Francis lis l’autre strophe mon grand: Teachers’ in-class use of nominal address forms with their students - Rehner, Katherine; Mougeon, Raymond; Mougeon, Françoise (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2023)
This study examines variation in the address forms teachers use in class with their students. It draws on a corpus collected in French-medium secondary schools in Ontario, Canada. The study provides a taxonomy of the nominal address forms used, along with frequency counts and dispersion rates. This includes forms used to address: i) the entire class (e.g., tout le monde ‘everyone’, guys, and les élèves ‘students’); ii) a group of students (e.g., ceux-celles/les gens, etc. + qui ‘those/the people, etc. + who’, les filles ‘girls’, and les gars ‘boys’); and iii) individual students (e.g., first names, first and last names, Monsieur ‘Sir’, Madame ‘Ma’am’, Mademoiselle ‘Miss’, ma belle ‘my dear’, mon grand ‘big guy’). The study examines the discursive functions associated with these address forms (e.g., positive relational functions like ‘praising’ and ‘encouraging’ are associated with terms of affection). The study concludes by highlighting the contribution its findings make to Francols’ (2010) calls for further research on the topic.